School and social inclusion in Italy: The contribution of associations for disabled people - Antonello Mura (Arizona State University, 2019)
The paper reflects on the historical and sociological dimensions that marked the emergence of disabled people associations in Italy. Through a historical analysis, we sought to define the context in which the first initiatives with association features were structured, directing the attention to their social and ethical dimensions. Their singularities were considered as integral parts of political-cultural events that influenced Italian perspectives on the schooling and social inclusion of disabled people in the 1970s. This analysis shows these associations have led to the reorganization of the services directed to disabled people, in the sense of affirming citizenship-promoter subjects and expanding innovative processes for the whole of society.